A lead-iron ore phase separation method, and a method for preparing ferroalloy and ferroalloy slag
By adding mineral particles of insoluble potassium or insoluble sodium salts during the iron removal process of wet zinc smelting and heat treatment, the problem of close bonding of lead-iron ore in iron alum slag is solved, and the problem of "iron ore phase in iron alum slag is achieved The effective separation of pyrlum and insoluble lead substances is reduced, reducing the difficulty and cost of treatment.
Patent Information
- Application Number
- CN202310319815.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-03-29
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2043-03-29
AI Technical Summary
During the wet zinc smelting process, the lead-iron ore phase in the iron alum slag caused by the pyrlum removal method is closely combined, resulting in large amount of slag and difficulty in resource recovery.
By adding mineral particles of insoluble potassium or insoluble sodium salt to the iron-lead mixture liquid and heat treatment under stirring, pyrlum crystals and insoluble lead substances are formed in a physically mixed state where they are independent of each other.
The pyrlum and insoluble lead substances are effectively separated, reducing the difficulty and cost of the treatment of pyrlum slag, and improving the iron removal rate and resource utilization rate.
Smart Images

Figure CN116462233B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to iron removal by ferroalloy method in the process of wet zinc smelting, and in particular to a lead-iron ore phase separation method and a preparation method of ferroalloy and ferroalloy slag. Background Art
[0002] The ferroalloy method was first used in the metallurgical industry in the 1960s to remove iron. The main reaction principle is that under certain conditions, 90% to 95% of Fe 3+ A Fe3(SO4)2(OH)6(A represents K + ,Na + ,NH4 + ,H3O + ) is precipitated out in the form of . Since the ferroalloy method for removing iron has the advantages of simple process, good filtration performance and controllable reaction conditions, it is widely used. For example, the leachate produced in the leaching stage of the wet zinc smelting industrial process contains iron ions and zinc ions. The prior art commonly uses the ferroalloy method for removing iron. After iron removal, the leachate enters the next step of electrolytic deposition process to produce zinc.
[0003] During the iron alum method of iron removal in wet zinc smelting, zinc roasted sand needs to be added as a neutralizing agent, which will bring in a large amount of insoluble heavy metal precipitates. In addition, lead and silver slag brought in by incomplete solid-liquid separation in the leaching stage, these solid impurities can serve as a substrate for the nucleation and growth of ferroalum, and are eventually wrapped by the slowly formed ferroalum to form a co-precipitate of ferroalum and heavy metals (such as lead sulfate) tightly combined. This is also one of the main reasons why this iron removal method produces a large amount of slag and the iron alum slag resource recovery is difficult.
[0004] The Chinese invention patent application with publication number CN115652104A discloses a method for preparing lead-free jaconite crystals, which can separate iron from the above-mentioned leachate and avoid the growth of jaconite on insoluble lead; the method comprises the following steps: S1, providing an iron-lead mixed solution, wherein the pH value of the iron-lead mixed solution is 0-1.4; S2, dripping alkali solution into the iron-lead mixed solution, and mixing the iron-lead mixed solution during the process of dripping the alkali solution to obtain a suspension containing amorphous iron minerals; S3, adding alkali metal salts and / or ammonium salts to the suspension to obtain a to-be-treated solution; S4, heat-treating the to-be-treated solution to obtain a final-treated solution; the final-treated solution contains lead-free jaconite crystals; wherein, before the to-be-treated solution is heat-treated, sulfate ions are provided to the to-be-treated solution.
[0005] Although the above patent application ensures the separation of iron and insoluble lead in the process of iron removal, it requires continuous dripping of alkali solution into the iron-lead mixture and the control of the proportion of iron in the amorphous iron mineral in the total iron element to ensure the separation of ferroaluminate crystals and insoluble lead. Therefore, the duration and amount of alkali solution dripping in the patent application need to be adjusted according to the state of the amorphous iron mineral, and the state of the amorphous iron mineral is not convenient to monitor in real time, which will affect its industrial application effect to a certain extent.
[0006] In view of this, it is necessary to provide a method for separating the lead-iron ore phase and a method for preparing ferrocyanide and ferrocyanide slag to solve or at least alleviate the technical defect of the close combination of the lead-iron ore phase in the above-mentioned ferrocyanide slag. Summary of the invention
[0007] The main purpose of the present invention is to provide a method for separating lead-iron ore phases and a method for preparing ferroalloy and ferroalloy slag, aiming to solve the technical problem of close combination of lead-iron ore phases in ferroalloy slag.
[0008] To this end, the present invention provides a lead-iron ore phase separation method based on the iron-lead mixed liquor iron alum method iron removal process, comprising the steps of:
[0009] S1, providing an iron-lead mixed solution, wherein the pH value of the iron-lead mixed solution is 0 to 1.4;
[0010] S2, adding a neutralizing agent to the iron-lead mixed solution to adjust the pH of the iron-lead mixed solution to 1.6-2.1, to obtain a first pretreated solution;
[0011] S3, adding a sparingly soluble potassium salt or a sparingly soluble sodium salt to the iron-lead mixed solution to obtain a second pretreated solution;
[0012] S4, heat-treating the second pre-treated liquid under stirring to obtain a final treated liquid;
[0013] The final treatment liquid contains ferroalloy residue, which includes ferroalloy crystals and insoluble lead substances, and the ferroalloy crystals and the insoluble lead substances are in a mutually independent physical mixed state;
[0014] Wherein, before the second pretreatment liquid is subjected to the heat treatment, sulfate ions are provided to the second pretreatment liquid.
[0015] Further, the method of providing sulfate ions to the second pretreatment liquid includes any one of the following:
[0016] Controlling the sulfate ion content in the iron-lead mixed solution;
[0017] introducing sulfate ions into the first pretreatment solution and / or the second pretreatment solution;
[0018] The iron-lead mixed solution is controlled to contain sulfate ions, and sulfate ions are introduced into the first pretreatment solution and / or the second pretreatment solution.
[0019] Furthermore, the iron ion concentration in the iron-lead mixture is 0.05-0.6 mol / L, and the lead in the iron-lead mixture comes from a sparingly soluble lead salt;
[0020] The sparingly soluble lead salt accounts for 0.1-2% by mass of the iron-lead mixed solution;
[0021] The molar ratio of potassium in the sparingly soluble potassium salt to iron in the iron-lead mixture is 1:3 to 3:1; the molar ratio of sodium in the sparingly soluble sodium salt to iron in the iron-lead mixture is 1:3 to 3:1;
[0022] The molar ratio of the sulfate ion to the iron element in the iron-lead mixed solution is 2:3 to 9:1.
[0023] Furthermore, the neutralizing agent includes one or more of roasted sand and zinc oxide.
[0024] Further, the sparingly soluble potassium salt includes one or more of potassium feldspar and muscovite; the sparingly soluble sodium salt includes one or more of albite and sodium pyroxene;
[0025] The particle sizes of the sparingly soluble potassium salt and the sparingly soluble sodium salt are both 20 to 100 μm.
[0026] Furthermore, the stirring rate is 400-600 r / min.
[0027] Furthermore, in step S4, the temperature of the heat treatment is 85-95° C., and the duration of the heat treatment is 3-5 hours.
[0028] Furthermore, the iron-lead mixed liquor includes a leachate produced in a leaching stage during a hydrometallurgical zinc smelting industrial process.
[0029] The present invention also provides a method for preparing ferroalloy, comprising the steps of:
[0030] S10, providing an iron-lead mixed solution, wherein the pH value of the iron-lead mixed solution is 0 to 1.4;
[0031] S20, adding a neutralizing agent to the iron-lead mixed solution to adjust the pH of the iron-lead mixed solution to 1.6-2.1, thereby obtaining a first pretreated solution;
[0032] S30, adding a sparingly soluble potassium salt or a sparingly soluble sodium salt to the iron-lead mixed solution to obtain a second pretreated solution;
[0033] S40, heat-treating the second pre-treated liquid under stirring to obtain a final treated liquid; the final treated liquid contains ferroalloy crystals;
[0034] Wherein, before the second pretreatment liquid is subjected to the heat treatment, sulfate ions are provided to the second pretreatment liquid.
[0035] The present invention also provides a method for preparing iron alum slag, comprising the steps of:
[0036] S100, providing an iron-lead mixed solution, wherein the pH value of the iron-lead mixed solution is 0 to 1.4;
[0037] S200, adding a neutralizing agent to the iron-lead mixed solution to adjust the pH of the iron-lead mixed solution to 1.6-2.1, thereby obtaining a first pretreated solution;
[0038] S300, adding a sparingly soluble potassium salt or a sparingly soluble sodium salt to the iron-lead mixed solution to obtain a second pretreated solution;
[0039] S400, heat-treating the second pre-treated liquid under stirring to obtain a final treated liquid;
[0040] S500, performing solid-liquid separation on the final treated liquid to obtain a separated liquid and iron alum slag;
[0041] Wherein, before the second pretreatment liquid is subjected to the heat treatment, sulfate ions are provided to the second pretreatment liquid.
[0042] Compared with the prior art, the present invention has at least the following advantages:
[0043] 1. The present invention adds mineral particles of sparingly soluble potassium salt or sparingly soluble sodium salt to the iron-lead mixed solution, which can provide more heterogeneous nucleation sites for jarosite crystallization, accelerate jarosite crystallization, and improve the iron removal rate; at the same time, the mineral particles can be used to slowly release potassium ions or sodium ions in the iron solution to provide alkali metal ions required for jarosite crystallization, form local supersaturation on the surface of the mineral particles, and form a lower heterogeneous nucleation energy barrier for jarosite than on the surface of sparingly soluble lead substances, so that jarosite selectively crystallizes on the surface of the mineral particles, inhibiting the jarosite from wrapping the sparingly soluble lead substances in the iron removal process, obtaining jarosite slag that is easy to handle, and greatly reducing the difficulty and cost of subsequent jarosite slag treatment and disposal.
[0044] 2. The present invention only requires replacing the soluble sodium salt or ammonium salt used in the actual process with mineral particles of insoluble potassium salt or insoluble sodium salt on the basis of the existing ferroaluminate iron removal process, without changing the existing process equipment and process, and at the same time reducing the cost of reagents; in addition, the added insoluble mineral particles are relatively large in size, and have a large difference in particle size and specific gravity from other insoluble particles in the ferroaluminate slag, so the separation performance is better, which is convenient for industrial promotion and application. BRIEF DESCRIPTION OF THE DRAWINGS
[0045] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the structures shown in these drawings without paying creative work.
[0046] Figure 1 This is a SEM image of muscovite in the precipitate magnified 4500 times after the reaction in Example 1 is completed;
[0047] Figure 2 This is a SEM image of lead sulfate in the precipitate after the reaction in Example 1 is completed, magnified 4500 times;
[0048] Figure 3 This is the X-ray diffraction (XRD) spectrum of the precipitate after the reaction in Example 1 is completed;
[0049] Figure 4 This is a SEM image of the precipitate magnified 3000 times after the reaction in Comparative Example 1 is completed;
[0050] Figure 5 This is a SEM image of the precipitate magnified 3000 times after the reaction in Comparative Example 2;
[0051] Figure 6 This is a SEM image of carbon nanofibers in the precipitate after the reaction in Comparative Example 3 is magnified 7000 times;
[0052] Figure 7 This is a SEM image of lead sulfate in the precipitate after the reaction in Comparative Example 3 is completed, magnified 2000 times.
[0053] The realization of the purpose, functional features and advantages of the present invention will be further explained in conjunction with the implementation methods and with reference to the accompanying drawings. DETAILED DESCRIPTION
[0054] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0055] Furthermore, the technical solutions of various embodiments of the present invention can be combined with each other, but they must be based on the fact that they can be realized by ordinary technicians in the field. When the combination of technical solutions is contradictory or cannot be realized, it should be considered that such a combination of technical solutions does not exist and is not within the protection scope required by the present invention. In addition, the "lead-free ferroaluminate crystals" in the present invention refer to the fact that the obtained ferroaluminate crystals basically do not have a situation where they are combined with the lead phase. Even if the two coexist in the ferroaluminate slag, the ferroaluminate and the lead phase (such as lead sulfate) are only in a mutually independent physical mixed state.
[0056] It should be understood that lead is one of the most important heavy metal impurity elements in ferrocyanide slag, most of which exists in the form of lead sulfate wrapped in ferrocyanide; according to statistics, a wet zinc smelting plant with an annual output of 100,000 tons of electrolytic zinc produces about 30,000 to 50,000 tons of ferrocyanide slag each year. In 2019, China's zinc production exceeded 6 million tons, and the amount of ferrocyanide slag produced exceeded 1.5 million tons; ferrocyanide slag has long been disposed of by stockpiling or direct landfill, and the current stockpile volume has exceeded 40 million tons, resulting in a huge waste of lead resources, while also posing a major pollution risk to the environment.
[0057] Based on this, in the process of treating the iron-lead mixed liquor, it is necessary to ensure that the lead-iron ore phase in the iron alum slag is in a separated state to reduce the difficulty of treating the iron alum slag, thereby ensuring the resource utilization of the iron alum slag.
[0058] To this end, the present invention provides a lead-iron ore phase separation method based on the iron-lead mixed liquor iron alum method iron removal process, so as to separate the lead-iron ore in the iron alum slag from the source, and ensure that the two are independent of each other in the iron alum slag; wherein, the iron alum method iron removal process can be understood as: the process of converting iron ions dissolved in the iron-lead mixed liquor into ferroalumina by the iron alum method, and the present invention also belongs to the iron alum method; the lead-iron ore phase separation can be understood as: in the iron alum slag, ferroalumina and insoluble lead substances are in a mutually independent physical mixing state.
[0059] The lead-iron ore phase separation method specifically comprises the steps of:
[0060] S1, providing an iron-lead mixed solution, wherein the pH value of the iron-lead mixed solution is 0-1.4.
[0061] S2, adding a neutralizing agent to the iron-lead mixed solution, adjusting the pH of the iron-lead mixed solution to 1.6-2.1, and obtaining a first pretreatment solution.
[0062] S3, adding sparingly soluble potassium salt or sparingly soluble sodium salt to the iron-lead mixed solution to obtain a second pretreatment solution.
[0063] S4, heat-treating the second pre-treated liquid under stirring to obtain a final treated liquid.
[0064] The final treatment liquid contains ferrocyanide slag, and after the final treatment liquid is subjected to solid-liquid separation, a separated liquid and the ferrocyanide slag can be obtained; the ferrocyanide slag includes ferrocyanide crystals and insoluble lead substances, and the ferrocyanide crystals and the insoluble lead substances are in a mutually independent physical mixed state.
[0065] Wherein, before the second pretreatment liquid is subjected to the heat treatment, sulfate ions are provided to the second pretreatment liquid.
[0066] The present invention also provides a method for preparing ferroalloy, comprising the steps of:
[0067] S10, providing an iron-lead mixed solution, wherein the pH value of the iron-lead mixed solution is 0 to 1.4.
[0068] S20, adding a neutralizing agent to the iron-lead mixed solution, adjusting the pH of the iron-lead mixed solution to 1.6-2.1, and obtaining a first pretreatment solution.
[0069] S30, adding a sparingly soluble potassium salt or a sparingly soluble sodium salt to the iron-lead mixed solution to obtain a second pretreatment solution.
[0070] S40, heat-treating the second pre-treated liquid under stirring to obtain a final treated liquid.
[0071] The final treatment liquid contains ferroaluminum crystals, which can be understood as lead-free ferroaluminum crystals; the ferroaluminum crystals are present in ferroaluminum slag, and after the final treatment liquid is separated into solid and liquid, a separated liquid and ferroaluminum slag can be obtained; the ferroaluminum slag includes the ferroaluminum crystals and insoluble lead substances, and the ferroaluminum crystals and the insoluble lead substances are in a mutually independent physical mixed state, thereby facilitating the separation of ferroaluminum from insoluble lead substances and facilitating the improvement of the lead grade.
[0072] Wherein, before the second pretreatment liquid is subjected to the heat treatment, sulfate ions are provided to the second pretreatment liquid.
[0073] The present invention also provides a method for preparing iron alum slag, comprising the steps of:
[0074] S100, providing an iron-lead mixed solution, wherein the pH value of the iron-lead mixed solution is 0 to 1.4.
[0075] S200, adding a neutralizing agent to the iron-lead mixed solution, adjusting the pH of the iron-lead mixed solution to 1.6-2.1, and obtaining a first pretreatment solution.
[0076] S300, adding a sparingly soluble potassium salt or a sparingly soluble sodium salt to the iron-lead mixed solution to obtain a second pretreatment solution.
[0077] S400, heat-treating the second pre-treated liquid under stirring to obtain a final treated liquid.
[0078] S500, performing solid-liquid separation on the final treated liquid to obtain a separated liquid and iron alum slag.
[0079] The ferroalloy slag includes the ferroalloy crystals and insoluble lead substances, and the ferroalloy crystals and the insoluble lead substances are in a mutually independent physical mixed state.
[0080] Wherein, before the second pretreatment liquid is subjected to the heat treatment, sulfate ions are provided to the second pretreatment liquid.
[0081] It should be pointed out that in the above-mentioned lead-iron ore phase separation method, the preparation method of ferrocyanide, and the preparation method of ferrocyanide slag, the various steps can be matched or replaced with each other.
[0082] As a further explanation of the above-mentioned lead-iron ore phase separation method, the preparation method of yttrium, and the preparation method of yttrium slag:
[0083] The iron-lead mixed solution can be derived from a liquid containing iron and lead, or can be prepared separately; the lead can be a poorly soluble lead substance, and the iron-lead mixed solution can also contain other ions (such as zinc ions) or other poorly soluble substances; the subsequent operations of the present invention are based on the iron-lead mixed solution.
[0084] In industry, the iron-lead mixed liquor may be derived from an acidic leaching liquor containing iron and / or from an acidic leaching liquor containing iron and lead; the iron-lead mixed liquor may specifically include or be a leaching liquor produced in the leaching stage of a hydrometallurgical zinc smelting industrial process; the leaching liquor generally contains iron ions and sparingly soluble lead salts, and may also contain zinc ions at the same time.
[0085] It should be explained that the insoluble lead substances entering the iron-lead mixture along with the neutralizer can also be included in the total amount of the insoluble lead substances in the iron-lead mixture; for example, when the neutralizer is a lead-carrying substance such as zinc roasted sand, the insoluble lead substances entering the iron-lead mixture along with the zinc roasted sand can also be included in the total amount of the insoluble lead substances in the iron-lead mixture.
[0086] The method of providing sulfate ions to the second pretreatment liquid may include or be any one of the following:
[0087] 1. Control the sulfate ions contained in the iron-lead mixed solution.
[0088] Specifically, it can be: taking a ferric sulfate solution, adding a sparingly soluble lead salt or other sparingly soluble lead substance to the ferric sulfate solution, so as to control the sulfate ion content in the iron-lead mixed solution; or directly taking a ferric sulfate solution containing sparingly soluble lead substances.
[0089] Alternatively, the acidic leaching solution containing poorly soluble lead is used as the iron-lead mixed solution; that is, the acidic leaching solution containing sulfate and iron ions is taken so that the iron-lead mixed solution contains sulfate ions.
[0090] 2. Introducing sulfate ions into the first pretreatment liquid and / or the second pretreatment liquid.
[0091] 3. Control the sulfate ions in the iron-lead mixed solution, and introduce sulfate ions into the first pretreatment solution and / or the second pretreatment solution.
[0092] Specifically, when sulfate ions exist in the iron-lead mixture but the amount of sulfate ions is insufficient for a sufficient reaction, the remaining sulfate ions to be supplemented may continue to be introduced into the first pretreatment solution and / or the second pretreatment solution.
[0093] It should be noted that in the process of controlling the sulfate ions contained in the iron-lead mixed solution and introducing sulfate ions into the first pretreatment solution and / or the second pretreatment solution, the sulfate ions cannot exist in the form of sodium sulfate, potassium sulfate, etc., so as to avoid the potassium ions and sodium ions provided by sodium sulfate and potassium sulfate from destroying the technical system of the present application (destroying the effects of sparingly soluble potassium salts and sparingly soluble sodium salts). Of course, in the process of forming yttrium, other elements that can destroy the effects of sparingly soluble potassium salts and sparingly soluble sodium salts in the present application cannot be introduced together with sulfate.
[0094] Exemplarily, to facilitate the implementation of the present invention, when controlling the iron-lead mixture to contain sulfate ions, the sulfate can exist in the form of ferric sulfate. At this time, the iron ions in the ferric sulfate can be included in the total amount of iron ions in the iron-lead mixture; when introducing sulfate ions into the first pretreatment liquid and / or the second pretreatment liquid, the sulfate can exist in the form of zinc sulfate.
[0095] Furthermore, the iron ion concentration in the iron-lead mixture can be 0.05-0.6 mol / L, and the lead in the iron-lead mixture comes from a sparingly soluble lead salt; the sparingly soluble lead salt can include or be one or more of lead sulfate, lead chloride, lead phosphate, and lead chromate; the sparingly soluble lead salt can account for 0.1-2% by mass of the iron-lead mixture.
[0096] Furthermore, the sparingly soluble potassium salt may be water-insoluble potassium salt mineral particles, and the sparingly soluble potassium salt may include one or more of potassium feldspar and muscovite; the sparingly soluble sodium salt may be water-insoluble sodium salt mineral particles, and the sparingly soluble sodium salt may include one or more of sodium feldspar and sodium pyroxene; the particle sizes of the sparingly soluble potassium salt and the sparingly soluble sodium salt may both be 20 to 100 μm.
[0097] When the sparingly soluble potassium salt is used, the molar ratio of the potassium element in the sparingly soluble potassium salt: the iron element in the iron-lead mixture is 1:3 to 3:1; when the sparingly soluble sodium salt is used, the molar ratio of the sodium element in the sparingly soluble sodium salt: the iron element in the iron-lead mixture is 1:3 to 3:1.
[0098] Furthermore, in order to ensure the progress of the reaction, the molar ratio of the sulfate ion: the iron element in the iron-lead mixture can be 2:3 to 9:1.
[0099] Furthermore, the neutralizing agent may include or be one or more of roasted sand and zinc oxide; the roasted sand may include or be zinc roasted sand; the actual amount of the neutralizing agent added is based on the ability to adjust the pH of the iron-lead mixture to 1.6-2.1.
[0100] Furthermore, the stirring rate is 400-600 r / min. It should be noted that the heat treatment must be carried out under stirring conditions, and the stirring rate should not be too high or too low.
[0101] Specifically, taking the sparingly soluble potassium salt as an example, due to the slow release of the sparingly soluble potassium salt, there are a large number of potassium ions only in the solid-liquid interface fluid layer on the surface of the sparingly soluble potassium salt, forming a supersaturated layer, and jaconite can rapidly heterogeneously nucleate and grow; while the potassium ion concentration in the liquid far away from the sparingly soluble potassium salt is low, and the nucleation and growth of jaconite is slow, thereby effectively avoiding the large-scale growth of jaconite on the sparingly soluble lead salt; therefore, the stirring rate can be no less than 400r / min to ensure that the iron ions must be in full contact with the sparingly soluble potassium salt.
[0102] However, when the stirring rate is too high, the supersaturated layer on the surface of the sparingly soluble potassium salt will be destroyed at the high stirring rate, resulting in the inability of jaconite to grow in large quantities on the surface of the sparingly soluble potassium salt; therefore, the stirring rate may not be higher than 600 r / min.
[0103] Furthermore, the temperature of the heat treatment may be 85-95° C., and the duration of the heat treatment may be 3-5 h.
[0104] In addition, step S2, step S20, and step S200 can also be carried out under heating conditions; that is, the iron-lead mixed solution can be heated to 85-95°C, kept warm at this temperature, and the neutralizer can be added to obtain the first pretreatment solution; thereafter, the temperature is continued to be kept warm for subsequent treatment until the reaction is completed.
[0105] Furthermore, those skilled in the art should be aware that after obtaining the iron alum slag, the iron alum slag can be subjected to differential centrifugation or gravity separation to obtain solids of ferroalloy (ferroalloy crystals) and solids containing insoluble lead substances. According to actual needs, those skilled in the art can also directly perform differential centrifugation or gravity separation on the final treated liquid during the solid-liquid separation process to separate the ferroalloy in the iron alum slag from other solids such as insoluble lead substances.
[0106] In the present invention, by adding the sparingly soluble potassium salt or the sparingly soluble sodium salt mineral particles to induce the crystallization of jarosite, the combination of iron, lead, etc. can be suppressed in the iron removal process, and the jarosite can be selectively crystallized on the surface of the sparingly soluble potassium salt or the sparingly soluble sodium salt mineral particles, thereby avoiding the wrapping of sparingly soluble lead substances (paringly soluble lead salts) by jarosite. In this way, it is helpful to achieve the effective separation of sparingly soluble lead substances and jarosite in the iron removal process of wet zinc smelting jarosite method, and greatly reduce the difficulty and cost of subsequent jarosite slag treatment and disposal.
[0107] In order to facilitate those skilled in the art to understand the invention in detail, examples are given below:
[0108] Example 1
[0109] 1. Take 400 mL of ferric sulfate solution, in which the iron ion concentration is 0.05 mol / L and the sulfate ion concentration is 0.075 mol / L; add 1.22 g of lead sulfate (particle size 15-20 μm; the same below, no further description) to the ferric sulfate solution, the mass of lead sulfate accounts for 0.3% of the total mass of the system, and obtain an iron-lead mixed solution with a pH of 1.4.
[0110] 2. The iron-lead mixture was heated to 95° C. with continuous stirring at a stirring rate of 500 r / min, and zinc oxide was added thereto to adjust the pH to 1.7 to obtain a first pretreatment solution.
[0111] 3. Add 2.65 g of sieved muscovite powder (150 mesh below and 250 mesh above) to the first pretreatment liquid to obtain a second pretreatment liquid.
[0112] In this embodiment, muscovite (KAl2(AlSi3O 10 The molar ratio of )(OH)2) to lead sulfate is basically 3:2; the potassium in the muscovite powder is basically 0.007 mol.
[0113] 4. The second pretreatment liquid was stirred and maintained at a temperature of 95° C. The stirring rate was 500 r / min. After stirring and reacting at 95° C. for 3 hours, a final treatment liquid was obtained.
[0114] After the reaction is completed, the final treated liquid is subjected to solid-liquid separation by suction filtration; after solid-liquid separation, the iron ion concentration in the solution is 0.002 mol / L, and the physical phases of the precipitate (iron alum residue) are lead sulfate, yttrium, and muscovite.
[0115] Energy dispersive spectrometer (EDS) measured that the iron content (mass percentage) on the lead sulfate surface was 2.2%, and the combination of ferroaluminate and lead sulfate was significantly inhibited; while the iron content (mass percentage) on the muscovite surface was 10.13%.
[0116] See also Figure 1 As shown, it can be seen that after 3 hours of reaction, more ferroaluminate (octahedral crystals) are formed on the surface of muscovite.
[0117] See also Figure 2 As shown, it can be seen that after 3 hours of reaction, only a very small amount of ferrocyanide (octahedral crystals) is formed on the surface of lead sulfate.
[0118] See also Figure 3 As shown, it can be seen that after 3 hours of reaction, the main phases in the precipitate are lead sulfate, ferrocyanide and muscovite.
[0119] Example 2
[0120] 1. Take 400mL of ferric sulfate solution, in which the iron ion concentration is 0.2mol / L and the sulfate ion concentration is 0.3mol / L; add 2.52g of lead sulfate to the ferric sulfate solution, the mass of lead sulfate accounts for 0.6% of the total mass of the system, and obtain an iron-lead mixed solution with a pH of 1.3.
[0121] 2. The iron-lead mixture was continuously stirred and heated to 90° C. at a stirring rate of 600 r / min, and zinc oxide was added thereto to adjust the pH to 1.6 to obtain a first pretreatment solution.
[0122] 3. Add 8.72 g of sieved sodium feldspar powder (250 mesh below and 500 mesh above) to the first pretreatment liquid to obtain a second pretreatment liquid.
[0123] In this embodiment, the molar ratio of albite (Na2O·Al2O3·6SiO2) to lead sulfate is substantially 2:1; and the sodium in the albite powder is substantially 0.034 mol.
[0124] 4. The second pre-treatment liquid was stirred and maintained at a temperature of 90° C. The stirring rate was 600 r / min. After stirring and reacting at 90° C. for 4 hours, a final treatment liquid was obtained.
[0125] After the reaction is completed, the final treated liquid is subjected to solid-liquid separation by suction filtration; after solid-liquid separation, the iron ion concentration in the solution is 0.016 mol / L, and the physical phases of the precipitate (iron alum slag) are lead sulfate, albite, and yttrium.
[0126] Energy dispersive spectrometer (EDS) measured that the iron content on the lead sulfate surface (mass percentage) was 3.5%, and the combination of jacinthite and lead sulfate was significantly inhibited; while the iron content on the albite surface (mass percentage) was 14.27%.
[0127] Comparative Example 1
[0128] 1. Take 400mL of ferric sulfate solution, in which the iron ion concentration is 0.05mol / L and the sulfate ion concentration is 0.075mol / L; add 1.22g of lead sulfate to the ferric sulfate solution, the mass of lead sulfate accounts for 0.3% of the total mass of the system, and obtain an iron-lead mixed solution with a pH of 1.4.
[0129] 2. Stir the iron-lead mixture and heat it to 95°C at a stirring rate of 500 r / min. During the stirring process, add 3 g of solid sodium nitrate to the iron-lead mixture, and then keep stirring and reacting at 95°C for 3 hours to obtain the final treated solution.
[0130] After the reaction is completed, the final treated liquid is subjected to solid-liquid separation by suction filtration; after solid-liquid separation, the iron ion concentration in the solution is 0.015 mol / L, and the physical phases of the precipitate (iron alum slag) are lead sulfate and ferroaluminate. The lead sulfate is obviously wrapped by ferroaluminate, and the iron content (mass percentage) on the surface of the lead sulfate is measured by energy dispersive spectrometer (EDS) to be 27.6%.
[0131] See also Figure 4 As shown, it can be seen that after the system with soluble sodium salt was reacted for 3 hours, a large amount of ferrocyanide grew on the surface of lead sulfate.
[0132] Comparative Example 2
[0133] 1. Take 400mL of ferric sulfate solution, in which the iron ion concentration is 0.05mol / L and the sulfate ion concentration is 0.075mol / L; add 1.22g of lead sulfate to the ferric sulfate solution, the mass of lead sulfate accounts for 0.3% of the total mass of the system, and obtain an iron-lead mixed solution with a pH of 1.4.
[0134] 2. The iron-lead mixture was heated to 95° C. with continuous stirring at a stirring rate of 500 r / min, and zinc oxide was added thereto to adjust the pH to 1.7 to obtain a first pretreatment solution.
[0135] 3. Add 1.2 g of nano iron oxide powder (the molar ratio of nano iron oxide to lead sulfate is 1.87:1) to the first pretreatment liquid, and then add 3 g of sodium nitrate solid to obtain a second pretreatment liquid.
[0136] 4. The second pre-treated liquid was stirred at 95° C. (stirring rate: 500 r / min) for 3 h to obtain a final treated liquid.
[0137] After the reaction is completed, the final treated liquid is subjected to solid-liquid separation by suction filtration; after solid-liquid separation, the iron ion concentration in the solution is 0.01 mol / L, and the physical phases of the precipitate (iron alum residue) are lead sulfate, yttrium and iron oxide. The lead sulfate is obviously wrapped by yttrium, and the iron content (mass percentage) on the surface of the lead sulfate is measured by energy dispersive spectrometer (EDS) to be 20.1%.
[0138] See also Figure 5 As shown, it can be seen that after the system with nano-iron oxide and soluble sodium salt reacted for 3 hours, a large amount of ferrocyanide grew on the surface of lead sulfate.
[0139] Comparative Example 3
[0140] 1. Take 400mL of ferric sulfate solution, in which the iron ion concentration is 0.05mol / L and the sulfate ion concentration is 0.075mol / L; add 1.22g of lead sulfate (the specific surface area of lead sulfate is 0.107m 2 / g), the mass of lead sulfate accounts for 0.3% of the total mass of the system, and an iron-lead mixed solution with a pH of 1.4 is obtained.
[0141] 2. The iron-lead mixture was heated to 95° C. with continuous stirring at a stirring rate of 500 r / min, and zinc oxide was added thereto to adjust the pH to 1.7 to obtain a first pretreatment solution.
[0142] 3. Add 0.5 g of carbon nanofiber (with a specific surface area of 850 m 2 / g), and then 3g of sodium nitrate solid was added to obtain the second pre-treated solution.
[0143] 4. The second pre-treated liquid was stirred at 95° C. (stirring rate: 500 r / min) for 3 h to obtain a final treated liquid.
[0144] After the reaction is completed, the final treated liquid is subjected to solid-liquid separation by suction filtration; after solid-liquid separation, the iron ion concentration in the solution is 0.006 mol / L, and the physical phases of the precipitate (iron alum residue) are lead sulfate, yttrium and carbon nanofibers. The lead sulfate is obviously wrapped by yttrium, and the iron content (mass percentage) on the surface of the lead sulfate is measured by energy dispersive spectrometer (EDS) to be 25.3%.
[0145] See also Figure 6 and Figure 7 As shown, it can be seen that after the system with carbon nanofibers and soluble sodium salts reacted for 3 hours, a small amount of ferrocyanide crystals appeared on the surface of the carbon nanofibers, and a large amount of ferrocyanide grew on the surface of lead sulfate.
[0146] The above technical solutions of the present invention are only preferred embodiments of the present invention, and the patent scope of the present invention is not limited thereto. All equivalent structural changes made by using the contents of the present invention specification and drawings under the technical concept of the present invention, or directly / indirectly applied in other related technical fields are included in the patent protection scope of the present invention.
Claims
1. A lead-iron ore phase separation method based on the iron-lead mixed liquor iron alum method iron removal process, characterized in that: Includes steps: S1, providing an iron-lead mixed solution, wherein the pH value of the iron-lead mixed solution is 0 to 1.4; S2, adding a neutralizing agent to the iron-lead mixed solution to adjust the pH of the iron-lead mixed solution to 1.6-2.1, to obtain a first pretreated solution; S3, adding a sparingly soluble potassium salt or a sparingly soluble sodium salt to the iron-lead mixed solution to obtain a second pretreated solution; S4, heat-treating the second pre-treated liquid under stirring to obtain a final treated liquid; The final treatment liquid contains ferroalloy residue, which includes ferroalloy crystals and insoluble lead substances, and the ferroalloy crystals and the insoluble lead substances are in a mutually independent physical mixed state; Wherein, before the second pretreatment liquid is subjected to the heat treatment, sulfate ions are provided to the second pretreatment liquid.
2. The lead-iron ore phase separation method according to claim 1, characterized in that: The method of providing sulfate ions to the second pretreatment liquid includes any one of the following: Controlling the sulfate ion content in the iron-lead mixed solution; introducing sulfate ions into the first pretreatment solution and / or the second pretreatment solution; The iron-lead mixed solution is controlled to contain sulfate ions, and sulfate ions are introduced into the first pretreatment solution and / or the second pretreatment solution.
3. The lead-iron ore phase separation method according to claim 1, characterized in that: The iron ion concentration in the iron-lead mixed solution is 0.05-0.6 mol / L, and the lead in the iron-lead mixed solution comes from insoluble lead salt; The sparingly soluble lead salt accounts for 0.1-2% by mass of the iron-lead mixed solution; The molar ratio of potassium in the sparingly soluble potassium salt to iron in the iron-lead mixture is 1:3 to 3:1; the molar ratio of sodium in the sparingly soluble sodium salt to iron in the iron-lead mixture is 1:3 to 3:1; The molar ratio of the sulfate ion to the iron element in the iron-lead mixed solution is 2:3 to 9:
1.
4. The lead-iron ore phase separation method according to claim 1, characterized in that: The neutralizing agent includes one or more of calcined sand and zinc oxide.
5. The lead-iron ore phase separation method according to claim 1, characterized in that: The sparingly soluble potassium salt includes one or more of potassium feldspar and muscovite; the sparingly soluble sodium salt includes one or more of albite and sodium pyroxene; The particle sizes of the sparingly soluble potassium salt and the sparingly soluble sodium salt are both 20 to 100 μm.
6. The lead-iron ore phase separation method according to claim 1, characterized in that: The stirring rate is 400-600 r / min.
7. The lead-iron ore phase separation method according to claim 1, characterized in that: In the step S4, the temperature of the heat treatment is 85-95° C., and the duration of the heat treatment is 3-5 hours.
8. The lead-iron ore phase separation method according to any one of claims 1 to 7, characterized in that: The iron-lead mixed liquor comprises the leaching liquor produced in the leaching stage during the hydrometallurgical zinc smelting industrial process.
9. A method for preparing ferroalloy, characterized in that: Includes steps: S10, providing an iron-lead mixed solution, wherein the pH value of the iron-lead mixed solution is 0 to 1.4; S20, adding a neutralizing agent to the iron-lead mixed solution to adjust the pH of the iron-lead mixed solution to 1.6-2.1, thereby obtaining a first pretreated solution; S30, adding a sparingly soluble potassium salt or a sparingly soluble sodium salt to the iron-lead mixed solution to obtain a second pretreated solution; S40, heat-treating the second pre-treated liquid under stirring to obtain a final treated liquid; the final treated liquid contains ferroalloy crystals; Wherein, before the second pretreatment liquid is subjected to the heat treatment, sulfate ions are provided to the second pretreatment liquid.
10. A method for preparing iron alum slag, characterized in that: Includes steps: S100, providing an iron-lead mixed solution, wherein the pH value of the iron-lead mixed solution is 0 to 1.4; S200, adding a neutralizing agent to the iron-lead mixed solution to adjust the pH of the iron-lead mixed solution to 1.6-2.1, thereby obtaining a first pretreated solution; S300, adding a sparingly soluble potassium salt or a sparingly soluble sodium salt to the iron-lead mixed solution to obtain a second pretreated solution; S400, heat-treating the second pre-treated liquid under stirring to obtain a final treated liquid; S500, performing solid-liquid separation on the final treated liquid to obtain a separated liquid and iron alum slag; Wherein, before the second pretreatment liquid is subjected to the heat treatment, sulfate ions are provided to the second pretreatment liquid.
Citation Information
Patent Citations
Lead-free jarosite crystal, jarosite slag, and preparation method and application of lead-free jarosite crystal and jarosite slag
CN115652104A
Method for removing iron with lead sulfate as vegasite-precipitating agent in wet zinc smelting process
CN102719666A
Iron vitriol slag treatment method
CN106011489A